Utility-Based Optimal Resource Allocation in LTE-A Networks by Hybrid ACO-TS with MFA Scheme. (13th March 2019) - Thayammal, Manju C; Mary Linda, M
Abstract: In mobile broadband technology, advanced long term evolution (LTE-A) networks support for a wide domain of communication services with various prerequisites. Resource allocation for each user equipment (UE) is one of the major and unique issues in wireless communication networks in which improper allocation of resource blocks (RBs) could minimize the throughput in LTE-A networks. RBs with aggregated carriers are deployed in these networks for the enhancement of bandwidth to achieve high speed and high rate data transmission. In this paper, utility-based optimal resource allocation scheme by hybrid ant colony optimization-tabu search (ACO-TS) with modified fit algorithm (MFA) is proposed. The proposed methodology involves three stages, (i) selection of UE with maximum data transmission rate, (ii) choosing RB with best channel quality indicator (CQI) index and (iii) assignment of RBs to each UE. The proposed framework is implemented in the working platform JAVA and the experimental results show that the proposed method attains better performance in terms of utilization rate and overall throughput.